Valuing whole complex lives: Young adults' experiences of recovery‐related principles in mental healthcare in the United States. (3rd October 2019) - Hughes, Shannon; Colbert, Robert; Baugh, Ashley
Abstract: One in five young adults (aged 18–25 years) in the United States experiences a past year mental disorder, commonly including depression or anxiety. Yet, 1.5 million each year do not receive needed mental health services and are unlikely, in general, to seek formal mental healthcare. We aimed to inform the development of a novel programme for young adult mental health by first eliciting their positive and negative prior experiences with mental health providers. Four focus groups with 19 young adults (aged 19–26 years) recruited from the community and with moderate to severe depression and/or anxiety were conducted in 2018 in a western US state. Participants' prior experiences with services/providers were elicited along six pre‐defined recovery‐related concepts: feeling listened to and validated, inclusivity, full information and consent, hope and optimism, connectedness, and change. Focus groups were audio‐recorded, transcribed verbatim and uploaded into NVivo version 12 software. Two independent coders used deductive thematic analysis to identify patterned responses. Feeling listened to and validated appeared as a cornerstone of other recovery concepts. Participants discussed past negative experiences with psychiatrists and regret for being put on medications in their teenage years without information or options. Hope and optimism were low because of a general focus by professionals to address immediate symptom‐based issues, rather than on improving their overall lives. Service providers' focus on medication‐taking, and other one‐size‐fits‐all tools, was interpreted as lacking a sincere desire to help. Young adults were particularly sensitive to inauthentic interactions and superficial strategies, which left them craving care that incorporated their whole lives, acknowledged biopsychosocial interconnections and prioritised improving their lives over 'feeling better' in a given moment. Mental health providers should consider developing programmes that shift focus away from an exclusively medical understanding of distress and towards holistic, educational or relational approaches that value body, mind, self‐exploration and authentic connection.